Emergency medical and legal assistance for victims of war-time rape - Vaida, Taras (ScienceRise: Juridical Science, 2023)
The relevance of the problem of crimes against sexual freedom (rapes), committed by the military men of the aggressor country in the temporarily occupied territories of Ukraine, is determined as a direct violation of domestic legislation and international norms of humanitarian law. The essence of the crime against sexual freedom and human inviolability as a socio-legal problem and a personal tragedy in the conditions of war is revealed. Attention is paid to the provision of psychological and pre-medical assistance to victims of sexual violence. The organizational and legal response measures of law enforcement agencies and other social institutions of the state to rapes, committed by the occupiers, are revealed, the procedure for investigation and documentation by a special mobile police group of facts of sexual violence by the occupiers is characterised. Recommendations for overcoming agraphobia are given. In order to provide effective emergency medical and legal assistance to victims of rape in wartime, prevention of agraphobia, it is advisable to take into account a set of conditions: 1) in order to minimize the victim’s destructive experiences of rape, it is advisable to use the technique of self-meditation and dissociation, to promote conviction about the guilt of the rapist-occupier; 2) pay attention to medical self-help, taking into account the existing contraindications to the use of available medical products, if possible, contact a gynecologist for a medical examination (avoidance of unwanted pregnancy); 3) provide operational information to law enforcement agencies about the facts of committed crimes, the location of victims, etc., to increase the efficiency of the investigation; 4) to conduct active monitoring of the specified problem by police units in the liberated territories; 5) to carry out mandatory documentation of the fact of the crime in accordance with legal requirements; 6) to take into account certain limitations in the attitude/communication with the injured person in order to avoid further psychological injury